Therapeutic Potential of Fulvic Acid in Chronic Inflammatory Diseases and Diabetes - John Winkler; Sanjoy Ghosh (Journal of Diabetes Research)
Chronic inflammatory diseases like diabetes are on a rise in the Western world. Based on the tsunami of new cases every year, new therapeutic measures must be considered. A promising avenue might involve the attenuation of underlying inflammation through natural health products (NHPs). This is because most NHPs have a rich history in traditional medicine and might be considered safer under appropriate doses and conditions. However, the biggest impediment in NHP research is that rarely do these products come with verified health benefits or dosing schedules established through modern scientific research. Fulvic acid (FvA), one such NHP, comes from humic substances produced by microorganisms in soil. Traditional medicine and modern research claim FvA can modulate the immune system, influence the oxidative state of cells, and improve gastrointestinal function; all of which are hallmarks of diabetes. This minireview outlines the available peer-reviewed research on FvA and examines its anecdotal health claims. We show that although available research has been minimal, there is substantial evidence to pursue FvA research in preventing chronic inflammatory diseases, including diabetes.